Highly efficient photoelectric effect in halide perovskites for regenerative electron sources - Fangze Liu (Nature Portfolio, 2021)
Electron sources play as important component in a wide range of applications. Here, the authors demonstrate efficient, regenerative, and low-cost electron sources based on solution-processed halide perovskite thin films with quantum efficiency up to 2.2% and a lifetime of more than 25 h.